2020
DOI: 10.3390/medicina56080376
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Markers of Myelodysplastic Syndromes

Abstract: Myelodysplastic syndrome (MDS) is a clonal disease characterized by multilineage dysplasia, peripheral blood cytopenias, and a high risk of transformation to acute myeloid leukemia. In theory, from clonal hematopoiesis of indeterminate potential to hematologic malignancies, there is a complex interplay between genetic and epigenetic factors, including miRNA. In practice, karyotype analysis assigns patients to different prognostic groups, and mutations are often associated with a particular disease phenotype. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…Towards the prognosis evaluations, blast cell percentage in bone marrow gives significant predictions for the disease course [ 9 ], where the risk of conversion to AML is directly proportional to the number of blast cells in the marrow and >20 % blast cells are categorized as AML [ 10 ]. Our patient had 13% of blast cells in his marrow, ruling out the transition of MDS to AML.…”
Section: Discussionmentioning
confidence: 99%
“…Towards the prognosis evaluations, blast cell percentage in bone marrow gives significant predictions for the disease course [ 9 ], where the risk of conversion to AML is directly proportional to the number of blast cells in the marrow and >20 % blast cells are categorized as AML [ 10 ]. Our patient had 13% of blast cells in his marrow, ruling out the transition of MDS to AML.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic markers gradually become more and more popular in describing MDS and allow MDS subtypes to be discriminated from each other. MDS is accompanied by genetic and epigenetic changes, including aberrant expression of miRNAs [13]. Nevertheless, from a fundamental point of view, further research is needed to understand the complex regulatory mechanisms between miRNAs and their target genes in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…did their best to present as fully as possible the data obtained from the studies of correlations between miRNA expression levels and MDS-specific karyotypes [ 85 ]. Unbalanced chromosomal abnormalities are characteristic of MDS, and the most common are del(5q), monosomy 7 or del(7q), trisomy 8 and del(20q) [ 88 ]. Alkhatabi et al .…”
Section: Micrornas and Genetic Changes In Mdsmentioning
confidence: 99%
“…Mutations are an integral part of the genetic changes leading to MDS; in particular, mutations to the SF3B1 , SRSF2, and U2AF1 genes involved in splicing are frequent in this disease [ 88 ]. It has been shown that the expression levels of let-7, miRNA-423, and miRNA-103a are decreased in MDS samples with mutations to these genes when compared with wild-type samples, suggesting the presence of complex molecular genetic cascades in MDS [ 93 ].…”
Section: Micrornas and Genetic Changes In Mdsmentioning
confidence: 99%
See 1 more Smart Citation